Pengaruh Latihan Lateral Feet Drill The Tanggo Dan Five Court Terhadap Kelincahan Otot Tungkai Pada Klub Galaxy Fc. Bima - Marzuki, Ismail; Soemardiawan, Soemardiawan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
The research objective is the slow movement of the feet in changing the direction of running due to the lack of agility (agility) in the players due to the ineffective training undertaken, the training methods that are not good in terms of running, attacking, passing and dribbling football are done slowly and easily grab the ball. The sampling technique used purposive sampling. The researcher used the entire population to be used as research samples, namely all Galaxy FC clubs totaling 20 active people, where the sample was divided into two, namely 10 Lateral Feet Drill The Tanggo players and 10 Five Court players. The research design used "One-Group. Pretest-posttest design ”(pre-test and final test) with the research method used by researchers, namely the method of observation, documentation method and method of test actions. based on statistical data analysis the conclusions of the above data results are: seen from the results of research X1 (lateral feet drill the tango) with Y the results of the model agility seen from tcount> ttable (¬¬5.092> 1.833). then the sound of the hypothesis is the effect of the lateral training feet drill the Tanggo on leg muscle agility in the Galaxy Fc club. Bima in 2020. the results of research X2 (five court) with Y results of agility seen from tcount> ttable (¬¬4.567> 1.833). with Y the agility obtained t count is much greater than t table, so it can be concluded that "there is an effect of five court training on leg muscle agility in the Galaxy Fc club. Bima 2020. accepted